Aktivitas Humas Membangun Citra dan Reputasi Kepolisian Di Polsek Bandung Kidul Melalui Kegiatan Bintara Sambang - Farid Alfarizi; Dedi Kurnia Syah Putra (Innovative: Journal Of Social Science Research, 2023)
This study discusses Public Relations activities to build the image and reputation of the police at the Bandung Kidul Polsek through non-commissioned officer activities. There were incidents that caused unrest and worry in the Bandung Kidul community, apart from that there were individuals in the Polri institutional body that caused losses to the POLRI itself, where the public's trust in the POLRI decreased and the image and reputation of the police was tarnished. Various efforts have been made by the Police to rebuild trust and also the image and reputation of the institution, one of which is through the Bintara Sambang activities. The purpose of this research is to find out how the non-commissioned officers' activities as a public relations activity build the image and reputation of the police at the Bandung Kidul Polsek. This study uses a qualitative approach, and narrative methods and the constructivism paradigm, to collect data the researcher conducts observations, interviews and documentation. The results of this study are that the activities of non-commissioned officers in Sambang carried out by all police personnel from the South Bandung Police, visit the community to stay in touch so that the closeness between the police and the community is established. As a result, police personnel from the Bandung Kidul Polsek carried out non-commissioned officer activities that directly came in contact with the community which was used as one of the Public Relations activities to build the image and reputation of the police at the Bandung Kidul Polsek.